Auditor change during listings: effect on IPO premiums - Ramadilli Mohd, Shamsher Mohamad; Ahmed, Huson Joher Ali (Universiti Putra Malaysia Press, 2001)
The study examined the relationship between choice of quality differentiated audit firm and initial return at listing. It is conjectured that the superior audit quality of Tier 1 audit firms helps to reduce ex-ante uncertainty and consequently reduces the initial premiums at listing. The findings show that there is an inclination for listed firms to engage Tier 1 audit firms, and no significant difference in the initial returns of IPOs firms audited by either Tier 1 or Non-Tier 1 audit firms were observed. However, higher significant initial returns for new issues were observed for Second Board firms relative to Main Board firms. The findings do not appear to suggest that the auditor reputation is a determinant of initial returns at listing. The findings are consistent with those documented by Shamsher and Annuar (1997) that investors are indifferent to the quality of audit service provided by Tier 1 and Non-Tier 1 audit firms.